The effects of Aeromonas hydrophila infection on oxidative stress, nonspecific immunity, autophagy, and apoptosis in the common carp. (April 2020) - Chen, Jianjun; Liu, Nana; Zhang, Huajie; Zhao, Yidi; Cao, Xianglin
Abstract: Although the toxicity of Aeromonas hydrophila infection to common carp has been characterized, the mechanisms underlying this toxicity have not been fully explored. The present study assessed the effects of A. hydrophila infection on oxidative stress, nonspecific immunity, autophagy, and apoptosis in the common carp ( Cyprinus carpio ). We measured the effects of 7.55 × 10 5 CFU/mL and 4.87 × 10 7 CFU/mL A. hydrophila on carp after 1, 3, 5, and 7 d of infection. GSH and SOD activity levels in the serum, liver, intestine, and gills generally increased during the early stage of infection, but significantly decreased ( P < 0.05) on the seventh day. In addition, MDA levels were significantly increased throughout the infection period. The activity levels of ACP, AKP, and LZM in the liver and intestine increased on the first day after infection, then decreased on the fifth and seventh days. The mRNA expressions levels of the autophagy-associated genes atg12, atg5, LC3-II, and BECN1 in the liver, kidney, and brain substantially increased on the third day after infection ( P < 0.05), while mTOR was significantly downregulated on the first and third days ( P < 0.05). Western blot analysis indicated that the ratio of LC3B-ǁ/LC3B-ǀ significantly increased ( P < 0.05) on days 3 and 5 post infection. Furthermore, the apoptosis-related gene Bcl-2 was significantly ( P < 0.05) upregulated in the liver, kidney, and brain of the treatment group on the first and third days, while caspase3 was significantly downregulated ( P < 0.05). In conclusion, our results demonstrate that A. hydrophila infection causes oxidative stress, stimulates nonspecific immune reactions, and results in autophagy in the common carp, possibly initiating apoptosis in the late stage of infection. The results of this study provide new insights into the mechanism of A. hydrophila infection in carp. Graphical abstract: Image 1 Highlights: The semi-lethal and non-toxic concentrations of carp infected with Aeromonas hydrophila. Oxidative stress is caused by Aeromonas hydrophila infection. Autophagy and apoptosis play an important role in the toxicological mechanism of carp.